Implementation and Validation of the SST Delayed eXtra-LES Model for Complex Turbulent Flows. Issue 6 (3rd July 2022) - Fracassi, Alessia; De Donno, Remo; Ghidoni, Antonio; Noventa, Gianmaria
Abstract : This work presents a Delayed version of the hybrid RANS-LES eXtra Large Eddy Simulation (SST DX-LES) model for the simulation of turbulent flows. In particular, in the proposed model the Shear Stress Transport (SST) k - ω turbulence model replaces the TNT k - ω model, and a shielding function is introduced to avoid the Modelled Stress Depletion (MSD) and the related Grid-Induced Separation (GIS), typical of DES-like hybrid models. Moreover, a different definition of the filter is used, which blends the formula based on the maximum element spacing and element volume. The proposed hybrid model is implemented in the open-source CFD software OpenFOAM, calibrated, validated and assessed on several benchmark cases. The results are compared with both experimental data and reference numerical results. Simulations are performed also with the original X-LES model to spotlight the accuracy improvement.